A Dual Photoelectrode Photoassisted Fe–Air Battery: The Photo‐Electrocatalysis Mechanism Accounting for the Improved Oxygen Evolution Reaction and Oxygen Reduction Reaction of Air Electrodes. Issue 7 (4th December 2021) - Qian, Bingzhi; Zhang, Yu; Hou, Xing; Bu, Degang; Zhang, Kai; Lan, Yalin; Li, Yuewen; Li, Shuo; Ma, Tianyi; Song, Xi‐Ming
Abstract: Effective utilization of solar energy in battery systems is a promising solution to achieve sustainable and green development. In this work, a photoassisted Fe–air battery (PFAB) with two photoelectrodes of ZnO–TiO2 heterostructure and polyterthiophene (pTTh)‐coated CuO (pTTh–CuO) grown on fluorine‐doped tin oxide (FTO) is proposed. The band structure of semiconductors and the charge‐transfer mechanism of heterostructure are studied. The electrochemical results show that the photogenerated electrons and holes play key roles in reducing the oxygen evolution reaction (OER)/oxygen reduction reaction (ORR) overpotential in the discharging and charging processes, respectively. The short‐circuit current density, the open‐circuit voltage, and the maximum power output of the PFAB can reach 34.28 mA cm −2, 1.15 V, and 5.69 mW cm −2 upon illumination, respectively. The photoassisted Fe–air battery exhibits a low charge voltage of 0.64 V for ZnO–TiO2 as photoelectrode and a discharge voltage of 1.38 V for pTTh–CuO as a photoelectrode at 0.1 mA cm −2 . Abstract : ZnO–TiO2 and polyterthiophene‐coated CuO (pTTh–CuO) electrode materials with excellent photo‐electrochemical activity and stability are designed. The approach of in situ conversion of energy from solar energy to electric energy inside the Fe–air battery is introduced. The proposed mechanism of organic/inorganic hybrid heterojunction provides an avenue for the design of semiconductor materials.